AAV-CRISPR/Cas9 Gene Editing Preserves Long-Term Vision in the P23H Rat Model of Autosomal Dominant Retinitis Pigmentosa - Saba Shahin; Hui Xu; Bin Lu; Augustus Mercado; Melissa K. Jones; Benjamin Bakondi; Shaomei Wang (MDPI AG, 2022)
Retinitis pigmentosa (RP) consists of a group of inherited, retinal degenerative disorders and is characterized by progressive loss of rod photoreceptors and eventual degeneration of cones in advanced stages, resulting in vision loss or blindness. Gene therapy has been effective in treating autosomal recessive RP (arRP). However, limited options are available for patients with autosomal dominant RP (adRP). In vivo gene editing may be a therapeutic option to treat adRP. We previously rescued vision in neonatal adRP rats by the selective ablation of the Rhodopsin S334ter transgene following electroporation of a CRISPR/Cas9 vector. However, the translational feasibility and long-term safety and efficacy of ablation therapy is unclear. To this end, we show that AAV delivery of a CRISPR/Cas9 construct disrupted the Rhodopsin P23H transgene in postnatal rats, which rescued long-term vision and retinal morphology.